Evaluasi Usability Pada Knowledge Management System (KMS) Menggunakan Metode System Usability Scale (SUS): (PT. Telekomunikasi Indonesia Witel Sumatera Selatan) - Mahdiyah Afifah Sari; Ken Ditha Tania (Jurnal Bisnis, Manajemen, dan Ekonomi, 2022)
An unattractive system interface and the lack of user motivation in using the Knowledge Management System (KMS) is one of the reason why usability testing is needed. Usability testing aims to determine the usability of the system, whether the system is in accordance with the purpose of its application. Usability Testing will uses System Usability Scale (SUS) method which involves users in the test. The results of this study are usability scores and recommendations for improvement that have been developed using the prototyping method based on the results of problem identification. This research can be used as a reference in the development of the system later.